MAKTABGACHA YOShDAGI BOLALARDA NUTQ BUZILIShLARINI TUZATISh JARAYONIDA LOGORITMIK TEXNOLOGIYALARNI QO‘LLASh - Bekmanova, J.A.; Tajimuratov, A.J. (SCIENCE and SOCIETY, 2025)
This article is devoted to an urgent issue in modern society — the characteristics of speech therapy work with preschool children exhibiting delayed mental development in preschool educational institutions, as well as the system of comprehensive corrective and educational measures aimed at overcoming speech disorders. The article presents scientifically grounded technologies for correcting speech deficiencies in preschool children through logorhythmic exercises and the application of logorhythmic technologies during these sessions.
Keywords: Logorhythmics; speech therapy; preschool children with disabilities; delayed mental development; speech; technology